The Analysis of Current Observations - Godin, Gabriel (The International Hydrographic Review, 2015)
A method is described for the approximate separation of the periodic and aperiodic processes contained in current observations. The short period irregularities, assigned mainly to turbulence, are first removed by applying a smoothing operator to the data. The low frequency band of the aperiodic process is then isolated with the help of a low pass filter. This low frequency variation is removed from the observations and the residues are analyzed for the presence of tidal constituents.